SYSTEM PENDUKUNG KEPUTUSAN DIAGNOSA PENYAKIT LAMBUNG MENGGUNAKAN METODE CBR - Mukhamad Fatkhur Roji; Muslim Alamsyah (SPIRIT, 2023)
Many people pay little attention to disorders of the stomach, both from a clean lifestyle and eating patterns due to busy daily activities. This has caused many people to experience gastric disorders to a serious and even difficult stage to treat as a result of not paying enough attention to the early symptoms of gastric disease. In this study, the method to be used is the CBR (Case Base Reasoning) method. Case Based Reasoning (CBR) Based on the results of research that has been done, that the CBR method can help diagnose stomach disease